Lack of consensus on an aging biology paradigm? A global survey reveals an agreement to disagree, and the need for an interdisciplinary framework. (October 2020) - Cohen, Alan A.; Kennedy, Brian K.; Anglas, Ulrich; Bronikowski, Anne M.; Deelen, Joris; Dufour, Frédérik; Ferbeyre, Gerardo; Ferrucci, Luigi; Franceschi, Claudio; Frasca, Daniela; Friguet, Bertrand; Gaudreau, Pierrette; et al.
Highlights: A recent symposium debate highlighted disagreements and confusion in aging biology. Symposium participants followed up by completing an online survey. Survey results show little common ground on most questions in aging biology. However, there is a near-consensus that aging is heterogeneous and multifactorial. Work is needed to achieve a common paradigm in aging biology. Abstract: At a recent symposium on aging biology, a debate was held as to whether or not we know what biological aging is. Most of the participants were struck not only by the lack of consensus on this core question, but also on many basic tenets of the field. Accordingly, we undertook a systematic survey of our 71 participants on key questions that were raised during the debate and symposium, eliciting 37 responses. The results confirmed the impression from the symposium: there is marked disagreement on the most fundamental questions in the field, and little consensus on anything other than the heterogeneous nature of aging processes. Areas of major disagreement included what participants viewed as the essence of aging, when it begins, whether aging is programmed or not, whether we currently have a good understanding of aging mechanisms, whether aging is or will be quantifiable, whether aging will be treatable, and whether many non-aging species exist. These disagreements lay bare the urgent need for a more unified and cross-disciplinary paradigm in the biology of aging that will clarify both areas of agreement and disagreement, allowing research to proceed more efficiently. We suggest directions to encourage the emergence of such a paradigm.